KOMPETENSI SISWA DALAM MENGGUNAKAN KALIMAT TRANSFORMASI - Dewi Maisah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
This study was conducted in order to describe the students' competence in using transformation sentence in Indonesian. Descriptive-quantitative method is applied to achieve the objectives of the study. The data source of this research is students’ essay of grade 5 MI Tahdzibiyah Gempolpading, Kecamatan Pucuk, Lamongan. The data are the transformation sentences transformations in it. The data collected by the test method, referring method , and the method of introspection. The results showed that the transformation phrase most used by students is compound sentence, while the least frequently used is the negative sentence. However, relating to the best grade, it is taken into account that the best result goes to negative sentences as the students reached 91, while the worst is the inversion sentence because the student reached only 47, and the most mistakes occurs at compound sentences.